Assessment of Agreement between Gates Method and Dual Plasma Sample Method for Measurement of Glomerular Filtration Rate (Bangladesh Journal of Nuclear Medicine, 2018)
Objectives: Glomerular filtration rate (GFR) is generally considered to be the best index of renal function in both healthy and diseased kidneys. Calculation of GFR plays a vital role in the management of patients having renal diseases. Clinicians can make their final decision regarding the potential need for kidney transplantation and also selection of a potential kidney donor. Many methods have been developed in order to obtain more accurate GFR values. The most popular radionuclide method is camera based Gates method using 99mTc DTPA (Diethylene triaminepentaacetic acid). This method can provide immediate calculation of individual kidney function as well as of global renal function. But several sources of errors may reduce the reliability of this method. Measurement of multiple blood samples offers almost real values of GFR, which have become the gold standard in clinical research. The aim of this research work was to study the agreement between Gates method and dual plasma sample method for measurement of GFR.Patients and methods: This cross sectional study was carried out in National Institute of Nuclear Medicine & Allied Sciences (NINMAS), during July 2015 to June 2016. A total of 59 patients were included in this study. GFR was estimated by both the camera based Gates method and dual plasma sample method (DPSM).Statistical analyses were carried out by using the Statistical Package for Social Sciences version 20.0 for Windows (SPSS Inc., Chicago, Illinois, USA). The mean values were calculated for continuous variables. Categorical data were expressed in percentage and number. Pearson correlation and Bland & Altman (B & A) analyses were applied for assessing correlation and agreement between Gates method and DPSM. Degree of relation between the variables is expressed by r (Pearson’s correlation coefficient).Results: The mean GFR evaluated by Gates method was found 82.2 ± 27.4 mL/min/1.73m2 and mean GFR by DPSM was found 82.8 ± 24.1 mL/min/1.73m2. A strong positive correlation (r = 0.833; p = 0.001) was found between the GFR values measured by Gates method and DPSM. With Bland and Altman analysis, it was observed that mean difference of GFR measured by Gates method and DPSM was – 0.6 ± 15.22 mL/min/1.73m2. The limit of agreement ranged from – 30.44 mL/min/1.73m2 to 29.24 mL/min/1.73m2.Conclusion: There was strong positive correlation between Gates method and DPSM for measurement of GFR. Mean difference between the methods was small. The bias between the methods was considered not significant. The differences within mean ± 1.96 SD are not clinically important. Hence Gates method and DPSM can reflect GFR almost equally and can be used interchangeably.Bangladesh J. Nuclear Med. 20(1): 19-23, January 2017